2016
DOI: 10.3389/fpls.2016.01700
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Nitrogen Balance and Productivity Analysis of Legume and Non-legume Supported Cropping Systems: The Potential Role of Biological Nitrogen Fixation

Abstract: The potential of biological nitrogen fixation (BNF) to provide sufficient N for production has encouraged re-appraisal of cropping systems that deploy legumes. It has been argued that legume-derived N can maintain productivity as an alternative to the application of mineral fertilizer, although few studies have systematically evaluated the effect of optimizing the balance between legumes and non N-fixing crops to optimize production. In addition, the shortage, or even absence in some regions, of measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 53 publications
0
52
0
Order By: Relevance
“…A multi‐stepped symbiosis between soil rhizobia and legumes results in the production of new root organs called nodules where inert atmospheric nitrogen (N) is converted into ammonia. This symbiosis sustainably provides the largest source of N to ecosystems (Bullock, ; Vitousek et al ., ; Jensen et al ., ; Iannetta et al ., ). Rhizobia infect root hair cells in the model legume Medicago truncatula by inducing and colonizing membrane invaginations called infection threads and they also simultaneously trigger cell divisions in several inner root layers which eventually form the nodule (Timmers et al ., ; Xiao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A multi‐stepped symbiosis between soil rhizobia and legumes results in the production of new root organs called nodules where inert atmospheric nitrogen (N) is converted into ammonia. This symbiosis sustainably provides the largest source of N to ecosystems (Bullock, ; Vitousek et al ., ; Jensen et al ., ; Iannetta et al ., ). Rhizobia infect root hair cells in the model legume Medicago truncatula by inducing and colonizing membrane invaginations called infection threads and they also simultaneously trigger cell divisions in several inner root layers which eventually form the nodule (Timmers et al ., ; Xiao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Biological N fixation varies in relation to the ability of legume species to fix N in different environmental conditions (Peoples et al, 2009). Across varying pedoclimatic regions of Europe it was shown that biological N fixation for different legume species ranges from 32 to 115 kg ha -1 annually (Iannetta et al, 2016). Our results show that the allocation of biologically fixed N in straw differed between forage and grain legumes.…”
Section: Discussionmentioning
confidence: 68%
“…Our results show that the allocation of biologically fixed N in straw differed between forage and grain legumes. Forage as opposed to grain crops in this range maintain high outputs of biomass and N tot (Iannetta et al, 2016). In Baltic region, clover was shown to accumulate up to 6.4-14.9 t ha -1 DM yield biomass and up to 118-327 kg ha -1 of N (Ingver et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N balance (Table 1) allows the comparison between the three systems as it was computed by averaging the variations related to the conditions in individual years and crops [30]. The adoption of TIC in ORG+ considerably improved the N self-sufficiency of this system [31], raising (+35%) the Ndfa as compared to ORG. As expected, the Noutput values confirmed the gap between organic and conventional farming systems [32]; the Noutput values observed in ORG+ were the lowest in accordance with the finding of Knapp and van der Heijden [33] and Cooper et al [34].…”
Section: Discussionmentioning
confidence: 99%